Influence of Farming Background in the Nutritional Status of Preschool Children in Jaffna peninsula - Umashankar, K.; Gowsala, T. (Sri Lanka Agricultural Economics Association, 2014)
Balanced food intake is a critical factor responsible for nutrition particularly in the case of children under five years of age. Understanding the determinants of poor nutritional attainment can provide better solutions to reduce child malnutrition in farming areas. Nutrition surveys use anthropometric measurements of pre-school children and infants as measures of nutritional status. For this study, the primary data were collected by administrating a pretested structured questionnaire. A purposive random sampling technique was used to collect the data. The sample constituted a total of 300 respondents. The collected data were analyzed within a framework of multivariate regression model. The analysis indicates that household per-capita expenditure is a leading determinant on nutritional status of pre-schoolers in farming areas of the Jaffna peninsula. Further, a negative effect of a child's age and sex were observed for height for age z-score, weight for age z-score and weight for height z-score. In the sampled population, 15.54 percent are underweight. The stunting is 20.49 percent and wasting is 13.78 percent. Stunting and underweight caused medium level malnutrition in the sampled population. Wasting results in high level of malnutrition present inthese preschool children. But the two extreme cases such as low level and high level of malnutrition do not occur in those children. In total sampled population, 34 percent of the preschool children of farming population have the problem of malnutrition in the form of stunting or wasting or underweight or all of themtogether. Children become more malnourished as they get older. The nutritional status of a child primarily depends on the quality and quantity of the food available at home; purchasing power of the household which would in turn determine the accessibility to food and the distribution of food within the household. Finally this research concludes that per-capita expenditure, age of child, sex of child, area of residence, and the parental education are associated with the nutritional status of preschool children in the farming area. Any effort that increases the farm households' income level and adult awareness regarding basic child nutrition requirement will improve the existing nutritionalsituation in Jaffna peninsula.
Keywords: Preschool children; Malnutrition; Farming background; Multivariate regression; Jaffna peninsula